2004
DOI: 10.1029/2003gl018770
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of x‐ray emission from rocket‐triggered lightning

Abstract: [1] We report measurements of the x-ray emission from rocket-triggered lightning, made during the summer of 2003, using four instruments placed between 15 and 40 m from the lightning channels. X-rays were measured 0 -80 ms just prior to and at the beginning of 73% of the 26 return strokes observed. The emission was composed of multiple, very brief bursts of x-rays in the 30-250 keV range, with each burst typically lasting less than 1 ms. The x-rays were primarily observed to be spatially and temporally associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
135
2
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 105 publications
(148 citation statements)
references
References 12 publications
9
135
2
2
Order By: Relevance
“…Figure 21, from Dwyer and Smith (2005), shows the RHESSI summed TGF spectrum along with the relativistic runaway (REAM) model at several altitudes, demonstrating that even TGFs deep in the atmosphere produce significant flux <100 keV, and that the best diagnostic of depth comes from the spectral slope in the range of approximately 0.5 MeV to 4 MeV. A comparison of the RHESSI TGF spectrum and the ground-level event seen by Dwyer et al (2004a) can be found in Dwyer (2009).…”
Section: Tgf Spectra and Source Altitudementioning
confidence: 92%
See 4 more Smart Citations
“…Figure 21, from Dwyer and Smith (2005), shows the RHESSI summed TGF spectrum along with the relativistic runaway (REAM) model at several altitudes, demonstrating that even TGFs deep in the atmosphere produce significant flux <100 keV, and that the best diagnostic of depth comes from the spectral slope in the range of approximately 0.5 MeV to 4 MeV. A comparison of the RHESSI TGF spectrum and the ground-level event seen by Dwyer et al (2004a) can be found in Dwyer (2009).…”
Section: Tgf Spectra and Source Altitudementioning
confidence: 92%
“…3.3). Carlson et al (2010b) note that neutrons seen from the ground due to a downwarddirected TGF should be accompanied by a detectable level of gamma-rays above 10 MeV, a phenomenon that has only been observed once, in triggered lightning (Dwyer et al 2004a). …”
Section: Interpretation Of Neutron Observationsmentioning
confidence: 99%
See 3 more Smart Citations